Pengaruh Pelatihan Manajemen Diri terhadap Perilaku Merokok pada Remaja Di SMK Negeri 2 Jember Kecamatan Sumbersari Kabupaten Jember (The Effect of Self-Management Training on Teenager’s Smoking Behavior at SMK Negeri 2 Jember of Sumbersari Sub-District Jember Regency) - Helda Puspitasari; Emi Wuri Wuryaningsih; Ahmad Rifai (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Smoking has become life among teenagers. Predisposisi factors of smoking behavior among teenage are psychological satisfaction to reduce their stress, peer pressure and try new things in life. One of the efforts to reduce negative effects of smoking habit is counseling through self management. This research aimed to analyze the effect of self-management training on teenager’s smoking behavior at SMK Negeri 2 Jember. The design of research was quasi experiment. The sample size was 15 respondents as control group and 15 respondents as treatment group. The t-test dependent showed the different of teenage smoking behavior before and after self-management training (intervention group p value= 0.000; CI = 95% and control group p value= 0.012; CI = 95%). The t-test independent showed the different about smoking behavior for the intervention group and the control group (p value= 0.000; CI = 95%). Self management technique consist of self monitoring, reinforcement positive, self contracting, and stimulus control. So, it can be concluded that self management training can decrease average by 6.5 cigarettes consumption in two weeks. Nurse is one of health practitioners who can increase their ability to show their role for health services for school by collaborating with educational department especially counseling teacher to implementing teenager’s smoking prevention program.Keywords: Self-management, counseling, smoking behavior, teenage